2014
DOI: 10.1111/jsr.12132
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems: predictor or outcome of media use among emerging adults at university?

Abstract: SUMMARYThe pervasiveness of media use in our society has raised concerns about its potential impact on important lifestyle behaviours, including sleep. Although a number of studies have modelled poor sleep as a negative outcome of media use, a critical assessment of the literature indicates two important gaps: (i) studies have almost exclusively relied on concurrent data, and thus have not been able to assess the direction of effects; and (ii) studies have largely been conducted with children and adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 27 publications
5
111
0
2
Order By: Relevance
“…The sample is self-selected and includes cross-sectional data only and may not have captured typical use by the average adolescent. It is not known whether the documented dose-response relationships between ED use and sleep would be observed in a population-representative sample or whether the association is due to reverse-causation (technology use could be a symptom not a cause of poor sleep [32]) or whether we would have observed the same patterns if we had phrased the exposure measure question differently. This study surveyed devices that were widely used in Australian popular culture in 2010/2011.…”
Section: Discussionmentioning
confidence: 96%
“…The sample is self-selected and includes cross-sectional data only and may not have captured typical use by the average adolescent. It is not known whether the documented dose-response relationships between ED use and sleep would be observed in a population-representative sample or whether the association is due to reverse-causation (technology use could be a symptom not a cause of poor sleep [32]) or whether we would have observed the same patterns if we had phrased the exposure measure question differently. This study surveyed devices that were widely used in Australian popular culture in 2010/2011.…”
Section: Discussionmentioning
confidence: 96%
“…In these cases, for example, someone with a pre-existing sleep condition may use SM as a pleasurable way to pass the time while awake or to distract him/herself from the distress of not sleeping. Indeed, there is some evidence that sleep problems predict longer duration of overall technology and media use, 37 and one study reported that using media as a sleep aid is a common practice among adolescents. 38 While that particular study did not assess social media use specifically, given the pervasive use of SM there may be good reason to believe that adolescents may also use SM as a sleep aid just as they use television and computer games.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all studies support the conclusion that media use increases risk for sleep problems in adolescents and emerging adults. A recent study of 942 college students found sleep problems (but not sleep duration) to predict increased time spent watching television and using social networking websites 1 year later but did not find evidence of television/social networking use predicting later sleep problems (Tavernier and Willoughby 2014). Given these unidirectional findings the authors concluded that ''emerging adults appear to seek out media as a means of coping with their sleep problems'' (Tavernier and Willoughby 2014).…”
Section: Electronic Media Usementioning
confidence: 95%